Pola Pastoral dalam Pertumbuhan Spiritual Jemaat Anak Hingga Dewasa di GKSI Syhallom Isong Raya, Kalimantan Barat - Hot Nome (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The community service activity at GKSI Syhallom Isong Raya, West Kalimantan, focuses on the spiritual growth of congregants from children to adults. The background of this community service (PKM) is the importance of pastoral patterns in shaping and maintaining the spiritual growth of Christians, in line with the teachings of Ephesians 4:11-16 regarding the need for every follower of Christ to grow and become like Christ. Although this church has been established since 2004 and has experienced growth in the number of congregants, there are significant challenges, namely the lack of participation from the younger generation in various church activities and an uneven level of spiritual maturity. Therefore, this PKM aims to provide a comprehensive overview of existing pastoral practices and present constructive input to strengthen the church's ministry. The results of the PKM indicate that effective pastoral patterns must be designed contextually and relevantly for each age group, focusing on building a strong foundation of faith from an early age for children, programs that address contemporary issues for teenagers and young adults, as well as fellowship through small groups and consistent pastoral support for adult congregants.